FALSE LUMEN BRANCHED STENT GRAFT IMPLANTATION FOR REPAIR OF A DISSECTING THORACOABDOMINAL AORTIC ANEURYSM - Catarino, Joana (2021)
Introduction: It is estimated that approximately 20 to 40% of patients with chronic type B aortic dissection (CTBAD) develop enlargement of the FL that warrants treatment. The standard endovascular treatment usually involves implant of a stent graft into the true lumen of the dissection in an effort to exclude the false lumen, with less morbidity than open surgery. Clinical case: The patient was a 65 year old male, with a prior history of hypertension, dyslipidemia and chronic kidney disease. He was referred to our vascular center for a CTBD, with thoracoabdominal aneurysm degeneration (Crawford type II) with a maximum diameter of 85mm. The celiac trunk, superior mesenteric and right renal artery arose from the false lumen and left renal artery from the true lumen. A three stage procedure was planned. The patient was first submitted to a carotid-subclavian bypass. Subsequently, a frozen elephant trunk procedure was undertaken and the TEVAR component was intentionally deployed on the false lumen. Lastly, a customized branched stent graft was implanted into the false lumen, with the right renal artery catheterized through a fenestration created for the effect. The angioCT at 1 month showed adequate proximal and distal sealing and permeable visceral branches. The true lumen was partially thrombosed. Conclusion: Implant of a branched graft into the false lumen of an aortic dissection in order to exclude a thoracoabdominal aortic aneurysm is possible, and can be a solution, with successful exclusion of the aneurysmal degeneration. The durability of this solution remains largely unknown and cautious follow-up is needed.